Penerapan Nilai-Nilai Islam dalam Konsep Desain Ruang Publik di Rumah Susun - Narida, Tisya Surya; Septanti, Dewi; Putri, Salsabila Adelia; Wulandari, Pristya Any (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Flats as an alternative alternative form of residence, must be able to provide a good quality of life. To determine the existing quality of life, a comprehensive study was carried out by identifying the character of the residents along with their occupation, income and educational background related to their behavior, especially towards public spaces and their use. Public space is the main focus of this research to empower the community economically considering that the majority of residents are low-income people. The design method used is a concept-based framework because it uses concepts as a way of organizing architectural responses. The main idea of designing public spaces in this research is the application of Islamic values because the population is Muslim. It is hoped that this design can be used as a recommendation for the design of public spaces in flats so that they are in accordance with Islamic values.